Remote Terminal Unit Developed for Distribution Automation System (DAS) using MPLAB Software - Ab Ghani, Mohd Ruddin; Wan Jusoh, Wan Nor Shela Ezwane; Raman, Siti Hajar; Mat Hanafiah, Mohd Ariff; Wan Hassan, Wan Ahmas Redhauddin (2013)
Remote terminal (RTU) is a standalone data acquisition and control unit which monitoring and control equipment at some remote location from the central station that utilizes in the Distribution Automation System (DAS). The functions of this RTU are acquisition of information such as measured values, signal, meter readings and RTU also can transmit command or instruction, set points, control variables and monitoring as a function of time. In the present Distribution Automation System(DAS), the distribution field of automation allows the utilities to implement flexible control of distribution system to enhance efficiency, reliability, and quality of electric service. The implementation of distribution automation system will be highlight based on two factors which are benefit of distribution automation system implementation and area of distribution automation system implementation. The hardware design uses PIC16F877A microcontroller to control all the function of RTU. The types of fault detected are under voltage and overcurrent. The design consists of MPLAB software development using C programming and hardware assembly. RTU also designed to communicate with the SCADA system and the result is RTU able to detect under voltage and overcurrent fault.